The Influence of Culture, Social, Personal, and Psychological Toward the Behavior of Choosing Islamic Finance: A Study in the Community of Aceh Province Indonesia - M. Yasir Nasution; Saparuddin Siregar; Hidayati Siregar (Budapest International Research and Critics University, 2021)
The high demand for motorbikes in the people of Aceh Province has led to an increase in the amount of motorcycle financing in the Province of Aceh. The purpose of this study is to find out and analyze how the behavior of the people of Aceh Province in choosing Islamic finance as a place for motorcycle financing. This study also aims to determine the obstacles and efforts made by Islamic finance companies so that the people of Aceh choose Islamic finance as a place of financing. Type of research is quantitative-qualitative method. The analysis technique used in quantitative research is the Structural Equation Model using AMOS 22.1 software, while qualitative research data are obtained through observation, interviews and documentation. The data analysis technique used in this study is an interactive model analysis consisting of data collection, data reduction, data presentation and conclusion drawing. This study produced cultural variables that produced P values (0.703), social variables with P values (0.070) and psychological variables with P values (0.395). Each of these variables does not affect the behavior of the people of Aceh Province in choosing Islamic finance as a place of financing. While the personal variable has a positive and significant effect on the P value (0.003) which is below the critical value of 0.05. While cultural, social, personal and psychological variables simultaneously do not affect people's behavior in choosing Islamic finance. Cultural variables on personal, cultural on psychological and social on psychological have a positive and significant effect, where each P value is brought to a critical value of 0.05. Personal variables and psychological variables do not have an indirect influence on the behavior of the people of Aceh Province in choosing Islamic finance with culture as an intervening variable. Likewise, personal and psychological variables do not have an indirect influence on the behavior of the people of Aceh Province in choosing Islamic finance with social as an intervening variable.